HUBUNGAN PERSEPSI SISWA TERHADAP KETERAMPILAN PENGELOLAAN KELAS OLEH GURU DENGAN HASIL BELAJAR GEOGRAFI DI SMA NEGERI 4 PARIAMAN - ayi sagita; Khairani Khairani (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to determine the relationship between student perceptions of classroom management skills by teac hers and learning outcomes of geography at SMAN 4 Pariaman. This research uses quantitative research that belongs to the type of correlation research, the sample in this study consisted of 106 students of class XI IPS SMAN 4 Pariaman, the sample selection was carried out by using a positive samplig method, namely as a part or representative of the population studied as many as 63 students. data collection techniques using a questionnaire or questionnaire given to students. Based on the research results, it can be concluded that the data analysis method used is the Product Moment correlation with a level of 5% is 0.386 means that r table. This is a relationship between student perceptions of classroom management skills and student learning outcomes. The product moment coefficient of 0.386% results in a determination coefficient of 14.4%. while the remaining 85.1% is influenced by other factors that are not discussed in this study.